PEMBELAJARAN TERPADU TIPE WEBBED: SUATU PENDEKATAN PEMBELAJARAN TEMATIK DI MI/SD - Syafrilianto Syafrilianto (IAIN Padangsidimpuan, 2019)
This article is a theoretical study to provide insight and understanding of webbed type integrated learning as one of the thematic learning approaches in MI / SD that are in line with the current 2013 curriculum.The webbed integrated learning is an integrated learning model that uses themes as the basis of learning by combining subject matter from multi disciplines or various subjects bound by one theme. Development of this approach begins by determining the specific themes that can be chosen between the teacher and the students, fellow teachers or students themselves. After the theme was agreed upon, it was followed by the selection of sub-themes with regard to their relation to other subjects. Furthermore, the sub-themes are planned for learning activities that students will do.The advantages of integrated learning webbed type for students is to obtain a complete view of the relationship of activities from different sciences.